Solving vehicular ad hoc network challenges with Big Data solutions. Issue 4 (1st July 2016) - Contreras‐Castillo, Juan; Zeadally, Sherali; Guerrero Ibañez, Juan Antonio
Abstract : The concept of vehicular ad hoc networks (VANETs) has emerged as an efficient way to improve the performance of transportation systems, enhance travel security and help address traffic control problems that modern society is facing today. Large amounts of VANET data are typically collected from highly heterogeneous sources paving the way for a new era of VANET‐Big Data. This data must be processed rapidly, efficiently and cost‐effectively by different users and systems to make timely decisions about traffic and transportation. VANET‐Big Data is causing a shift from technology‐driven to data‐driven VANETs. The authors analyse and discuss Big Data solutions that can be leveraged to address some of the emerging challenges of VANETs.